Rare adverse effects of anti tuberculous therapy − a case series - Neeraj Sharma; Kunal Kumar; Sarvinder Singh; Puneet Saxena; Nalin Singh; Akhil Kollammarukudy Ravi (The Journal of Association of Chest Physicians, 2023)
Tuberculosis is prevalent throughout the world and is a major public health problem in most developing countries. Standardized and directly observed treatment under NTEP (National Tuberculosis Elimination Programme) is currently recommended for drug-sensitive pulmonary tuberculosis in India. It is generally well tolerated, with few minor side effects. Severe side effects necessitating discontinuation of therapy are rare with standard TB treatment regimens. Drug-resistant tuberculosis (DR-TB) has become more common in recent years, posing a challenge to global efforts to control the disease. Therapy for DR-TB has been associated with many adverse effects. Therefore, close monitoring of patients on DR-TB therapy is necessary to ensure that adverse effects of drugs are recognized early by healthcare personnel and treated accordingly. This will improve drug compliance and, hence, treatment goals. Here we report three cases of tuberculosis who had unusual adverse effects while receiving anti-tuberculous medication, prompting drug discontinuation.